CAL-1 as Cellular Model System to Study CCR7-Guided Human Dendritic Cell Migration - Uetz-von Allmen, Edith; Samson, Guerric P. B.; Purvanov, Vladimir; Maeda, Takahiro; Legler, Daniel F. (Frontiers in Immunology, 2021)
Dendritic cells (DCs) are potent and versatile professional antigen-presenting cells and central for the induction of adaptive immunity. The ability to migrate and transport peripherally acquired antigens to draining lymph nodes for subsequent cognate T cell priming is a key feature of DCs. Consequently, DC-based immunotherapies are used to elicit tumor-antigen specific T cell responses in cancer patients. Understanding chemokine-guided DC migration is critical to explore DCs as cellular vaccines for immunotherapeutic approaches. Currently, research is hampered by the lack of appropriate human cellular model systems to effectively study spatio-temporal signaling and CCR7-driven migration of human DCs. Here, we report that the previously established human neoplastic cell line CAL-1 expresses the human DC surface antigens CD11c and HLA-DR together with co-stimulatory molecules. Importantly, if exposed for three days to GM-CSF, CAL-1 cells induce the endogenous expression of the chemokine receptor CCR7 upon encountering the clinically approved TLR7/8 agonist Resiquimod R848 and readily migrate along chemokine gradients. Further, we demonstrate that CAL-1 cells can be genetically modified to express fluorescent (GFP)-tagged reporter proteins to study and visualize signaling or can be gene edited using CRISPR/Cas9. Hence, we herein present the human CAL-1 cell line as versatile and valuable cellular model system to effectively study human DC migration and signaling.